Aprovechamiento de orujo de uva borgoña negra (vitis labrusca) en bolsa filtrante - Fernandez Pezo, Damaris de los Angeles (2013)
The present work is aimed at the production of a filtering product, using fresh fermented pomace of grape. The variety of grape that was used for the production of the wine, is the black burgundy (Vitis labrusca) or lsabella; that possesses low content of soluble solids, high acidity, good fragrance and color; being the only variety of grape cultivated in the Region St Martin. The pomace is obtained in the stage of the devatting of the wine. The investigation consisted initially in evaluating and determining the temperatures and drying times optima!, applicable during the drying of the grape pomace, until a maximum final humidity of the 10 o/o (lndecopi, 2010); and was selected batches that fulfilled with this request. In the next stage, we evaluated the percentage of total phenols and tannins that was presenting every selected batch; and there was chosen the batch that had the major quantity of these functional compounds. With the data of the chosen batch, arose a flowchart with the optimal parameters to obtain of grape pomace FilterThe definitive stage consisted in the production of the grape pomace filtering and its physicist and chemistry characterization (humidity, ashes, fat, fiber, acidity, total phenols and tannins) and microbiological (viable aerobios mesofilos, coliforms, Escherichia coli, molds, leavens and Sa/monella sp). The infusion of grape pomace filtering; was subjected to a sensory analysis, by means of an affective test (verbal 5-point hedonic scale method), where was determinad that the aroma (fragrance) is the attribute of organoleptic quality of greater consumar acceptance. To evaluate comparatively the content of total phenols and tannins, from the raw material (grape pomace fermented fresh), the finished product (grape pomace fermented dried and ground}, until the infusion of grape pomace filtering, were obtained significant variations between samples.